2021
DOI: 10.1136/bmjopen-2020-042729
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic changes in the spinal extensor musculature in patients experiencing chronic spinal pain: protocol for a systematic review

Abstract: IntroductionChronic spinal pain (CSP) is the most common musculoskeletal disorder and is a leading cause of disability as per the Global Burden of Diseases. Previous reviews of microscopic changes in the spinal extensor muscles of people with CSP have focused on the lumbar region only and the results have been inconclusive. Therefore, in this protocol, we aim to assess microscopic changes in the extensor muscles of all spinal regions, investigating regionally specific changes in muscle fibre types of the spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The p<.05 was considered significant. Statistical heterogeneity was analyzed using the I 2 statistic with 25%, 50%, or 75% indicating low, moderate and high heterogeneity between the studies respectively as indicated in the protocol [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The p<.05 was considered significant. Statistical heterogeneity was analyzed using the I 2 statistic with 25%, 50%, or 75% indicating low, moderate and high heterogeneity between the studies respectively as indicated in the protocol [32].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the systematic review was designed using PRISMA-P guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols) [28] and the Cochrane handbook for systematic reviews [29−31]. The protocol was registered under PROSPERO (CRD42020198087) and published [32]. This systematic review is reported in line with the PRISMA statement [28] as presented in Appendix 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation